The development of pre-registration occupational therapy student perceptions of research and evidence-based practice: A Q-methodology study - Tanya Rihtman; Mike Morgan; Julie Booth (Taylor & Francis Group, 2024)
Background Pedagogically sound curricula are needed for occupational therapy (OT) students to adopt evidence-based practice (EBP) principles and internalise EBP within their professional identities. Exploring students' perceptions of this knowledge area can contribute to effective curriculum design.Aims/Objectives To explore the evolution of pre-registration OT student perceptions of research and EBP over the course of their engagement with undergraduate teaching and learning.Materials and methods The Q-sort approach synthesises different viewpoints regarding a sample of statements, using by-person factor analysis (respondents = variables; statements = sample). Final year pre-registration OT students completed the same Q-sort at three timepoints (pre-dissertation [n = 18]; post-dissertation submission [n = 12]; post-student research conference [n = 6]). Q-sort responses were intercorrelated and factor-analysed; extraction of factors with an eigenvalue of ¬>0.9 and varimax rotation identified majority viewpoints.Results Significant factors were revealed at each timepoint: 1a: 'Evidence-inseparable from OT practice', 1b: 'Research for research's sake-inseparable from the occupational therapy identity', 2: 'Who am I to question the gurus?', 3: 'I can do it with confidence...but so what?'Conclusions Opportunities for completing 'authentic' student research projects, with 'ownership' of results, may enhance research and EBP confidence and professional identity.Significance Findings expand current knowledge regarding effective use of pre-registration educational opportunities to support future research and EBP.